الأعراض النفس جسمیة وعلاقتھا بالإنجاز الریاضي لدى الملاكمین المتقدمین - فراس عبد المنعم عبد الرزاق (physical education and sport sciences college for women/ Baghdad University, 2018)
Aim of the research to identify the symptoms Alnevsjsmah and achievement of the boxers. The researcher used the descriptive method survey of suitability nature of the problem, either the research sample was tested (50) Player of Diyala clubs participating in the Iraq Clubs Championship category of applicants, which represents community Find random way, the researcher conducting an experiment major search through the distribution of the questionnaire Attached supplements in search research sample of (32) Player before the beginning of Nazlat directly. Then calculated the results of bout by the rulers (judges) Number (5) spread on the sides of the ring., After the researcher used statistical bag of Social Sciences (spss) to deal with the results of his research, which included (mean, standard deviation, and testing (person). And reach Researcher to a set of conclusions most importantly, the results showed that the percentage of those who answered was (36.75%) and who answered (do not) was (63.25%) as well as the results indicated the emergence of symptoms of the same physical high proportion of the boxers who answered 'yes' than impact on the level of their achievement. The results indicated the